Encyclopedia of Criminal Activities and the Deep Web 2020
DOI: 10.4018/978-1-5225-9715-5.ch058
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Spamming Attacks to Blogging Websites and Their Security Techniques

Abstract: With the explosive expansion of information on the world wide web, search engines are becoming more significant in the day-to-day lives of humans. Even though a search engine generally gives huge number of results for certain query, the majority of the search engine users simply view the first few web pages in result lists. Consequently, the ranking position has become a most important concern of internet service providers. This article addresses the vulnerabilities, spamming attacks, and countermeasures in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Following it, the crawlers try to use the Web mining methods. Finally, crawlers perform distributed denial of service and remove the sites for quite a while (Vishwakarma and Jain, 2020; Rahman et al , 2020; Koloveas et al , 2021; Xu et al , 2018). It is disagreeable in any circumstance, especially in banking, as the data is sensitive.…”
Section: Related Workmentioning
confidence: 99%
“…Following it, the crawlers try to use the Web mining methods. Finally, crawlers perform distributed denial of service and remove the sites for quite a while (Vishwakarma and Jain, 2020; Rahman et al , 2020; Koloveas et al , 2021; Xu et al , 2018). It is disagreeable in any circumstance, especially in banking, as the data is sensitive.…”
Section: Related Workmentioning
confidence: 99%
“…Many surveys have shown that the increase in the dependence on credit cards to perform financial transactions is accompanied by an increasing rate of fraud, as seen in [1,3]. The increasing capabilities of the attackers or the hackers have accentuated the problem since these people can exploit security gaps to obtain sensitive information about users or their credit information to perform malicious activities, such as fraud [4,5]. To define this problem accurately, Fig.…”
Section: B Problem Statementmentioning
confidence: 99%
“…Credit card fraud is the fraudulent use of credit card details to buy a product or service. These transactions can be physically or digitally performed [5]. In physical transactions, the credit card is physically present.…”
Section: Introductionmentioning
confidence: 99%